Effect of protein restriction of Angus cows during late gestation: Subsequent reproductive performance and milk yield - Lopez Valiente, Sebastian; Maresca, Sebastian; Rodriguez, Alejandro Martin; Palladino, Rafael Alejandro; Lacau Mengido, Isabel M.; Long, Nathan M.; Quintans, Graciela I. (2018)
The effect of level of CP fed during late gestation on reproductive performance and milk production was studied in multiparous cows. Sixty-eight pregnant Angus cows were used. At 121 d prepartum, cows were blocked by BW (409 ± 57 kg) and expected calving date, randomly assigned to a low-protein (LP = 6% CP) or high-protein diet (HP = 12% CP), and allocated to 12 pens per treatment. After parturition, all cows were managed in a single group until weaning. Body weight and BCS were determined at the start of the experiment, at calving, and at weaning. Nonesterified fatty acids, insulin, IGF-1, and glucose were determined every 24 d prepartum and nonesterified fatty acids and glucose every 38 d postpartum. Progesterone was quantified weekly to indicate luteal activity and estimate interval to first estrus. Milk production was measured until weaning. The HP cows had greater BW gain during the prepartum period (P < 0.01) and tended to gain more BCS (P = 0.06) than LP cows. The prepartum diet did not affect gestation length (P = 0.44) or interval from calving to the onset of luteal activity (P = 0.35). Pregnancy rates, milk quality, and production were not influenced by dietary treatments. Cows in the HP treatment had greater prepartum serum urea concentrations than LP treatment (P < 0.05). In conclusion, protein level prepartum in multiparous beef cows affected the BW change at calving, without consequences on reproductive performance and milk quality and yield.